Features of the Relationship Between Urbanisms and Historical Memory (on the Materials of Kharkiv) - Удовенко, Лідія (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2018)
In the article the basis of archival, field materialsdemonstrate the mutual relationship of historical memory and informal urbanonyms used in the speech of citizens. It is defined, how the concrete toponym is connected with the person's identification with himself. It is reported about the toponyms seized by the authorities from the toponymy of the city, which the townspeople continue to use in oral speech. The author makes a conclusion about the reasons for keeping officially abolished toponyms in the memory of the urban community.